THE CONTRIBUTION OF COMMUNITY-BASED TOURISM TO HOUSEHOLD INCOME: EVIDENCE FROM WEST KALIMANTAN, INDONESIA - Thomas Oni Veriasa; Arif Aliadi; Agung Nugroho; Febri Sastiviani Putri Cantika; Ivonne BR Panggabean; Sigit Purwanto; Alias; Devie Septria (Indonesian Journal of Forestry Research, 2023)
Tourism has long been considered as a way to preserve a conservation area. It can increase community participation, job creation, local economy, and reduce conflicts in conservation areas. Community-based tourism (CBT) has been conducted intensively in Bukit Baka Bukit Raya National Park (BBBRNP) area since 2017 as a strategy for the national park to engage the local community and maximise socio-economic benefit. This study investigates the contribution of CBT to the rural economy in the buffer area in BBBRNP, especially in the Rantau Malam Village. First, the study aims to assess the contribution of CBT to community income using household income analysis; second, to analyse the influencing factors of CBT income on household poverty using two-stage least squares (2SLS). This result shows that CBT has a low contribution to the total household income, which is only 1.7% per year, before the Covid 19 outbreak in early 2020. The simultaneous regression analysis also shows that the CBT income does not significantly influence household poverty and vice versa. Three factors significantly influence CBT income: saving, family size, and community engagement. Furthermore, household income, diversification income, and productive assets significantly influence the per capita expenditure. Further development of the CBT should pursue a significant household income contribution and equitable distribution of benefits by developing business models, involving more communities and strengthening support from various parties.